Complications and Mortality Rates Following Surgical Management of Extradural Spine Tumors in New York State. Issue 7 (1st April 2020) - Williams, Devin M.; Thirukumaran, Caroline P.; oses, Jalea T.; Mesfin, Addisu
Abstract : Study Design: Database analysis. Objective: To evaluate complications and mortality in patients undergoing surgical management of extradural spinal tumors in New York State. Summary of Background Data: Metastatic spine surgery has a high rate of complications but most studies are limited to single institutions. Methods: The Statewide Planning and Research Cooperative System was used to identify patients with extradural spinal tumors undergoing surgery in New York State from 2006 to 2015. Bivariate and multivariate logistic regression analyses were used to estimate outcomes. Results: Four thousand seven hundred sixty-seven patients were identified, the majority of patients were male and white a median age of 61. The complication rate was 17.6% and the mortality rate within 30 days of discharge was 12.2%. Multivariate analysis showed the odds of complications were higher in males compared with females (odds ratio [OR]: 1.27; 95% confidence interval [CI]: 1.05–1.52, P  = 0.01), and patients on Medicaid compared with patients on private insurance (OR: 1.42; 95% CI: 1.03–1.96, P  = 0.03). Analysis of hospital characteristics showed lower volume hospitals (OR 1.48; 95% CI: 1.03–2.13, P value = 0.03), and teaching hospitals (OR: 1.47; 95% CI: 1.03–2.09, P  = 0.04), have higher odds of complications compared with high-volume hospitals and nonteaching hospitals. Multivariate analysis showed higher odds of mortality within 30 days of discharge in patients of older age (OR: 1.02; 95% CI: 1.01–1.03, P value = 0.001), low-volume hospitals compared with high-volume hospitals (OR: 1.36; 95% CI: 1.09–1.79, P value = 0.02), hospitals with low bed size compared with high bed size (OR: 1.43; 95% CI: 1.12–1.83, P value = 0.01), and urban hospitals compared with rural hospitals (OR: 3.04; 95% CI: 2.03–4.56, P value = 0.001). Conclusion: Low-volume hospitals are associated with complications and mortality in patients with metastatic spine disease. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textSPARCS was used to identify 4767 patients undergoing extradural spinal tumor surgery in New York State. Complications were higher in males, patients on Medicaid, lower volume hospitals, and teaching hospitals. Mortality was higher in patients of older age, low-volume hospitals, hospitals with low bed size and urban hospitals.